1993
DOI: 10.1111/j.1528-1157.1993.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Intractable Infantile Spasms: Neuroimaging Perspectives

Abstract: Twenty-three infants and children underwent cortical resection (n = 15) or hemispherectomy (n = 8) for intractable infantile spasms. Infantile spasms were present at the time of surgery in 17 of the 23 patients; in six, spasms had evolved to other seizure types during surgical evaluation. Children with a remote history of infantile spasms were excluded from this study. Focal or hemispheric lesions were identified by magnetic resonance imaging in seven children; an additional two showed focal atrophy without a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
5
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(158 citation statements)
references
References 27 publications
8
144
5
1
Order By: Relevance
“…The combination of MRI and CT, however, correctly localised only 17% of patients; the majority of scans were non-localising with 21% partially localised and no incorrectly localised scans. 38 NIRS localised a seizure focus in all patients, with 28 of the 29 scans being correctly localised and one incorrectly localised.…”
Section: Othermentioning
confidence: 99%
See 3 more Smart Citations
“…The combination of MRI and CT, however, correctly localised only 17% of patients; the majority of scans were non-localising with 21% partially localised and no incorrectly localised scans. 38 NIRS localised a seizure focus in all patients, with 28 of the 29 scans being correctly localised and one incorrectly localised.…”
Section: Othermentioning
confidence: 99%
“…A number of other studies reported one or more evaluations for which it was not possible to calculate an RR, but other evaluations that were included. 29,38,40,62 None of the studies included in this section included an appropriate patient spectrum. Twenty-four studies defined a good outcome following surgery as Engel class I or II and the remaining eight studies defined a good outcome as being seizure free following surgery.…”
Section: Association Of Seizure Focus Localisation With Outcome Follomentioning
confidence: 99%
See 2 more Smart Citations
“…Some children with infantile spasms show areas of regional hypometabolism on PET, and surgical resection of these areas has been associated with dramatic improvement in some instances (56). PET is also a useful research tool for performing in vivo neuropharmacologic studies in patients with epilepsy, and the effects of AEDs (57), localized upregulation of opiate receptors (58), and locally decreased benzodiazepine receptors (59) have been demonstrated.…”
Section: Functional Brain Imagingmentioning
confidence: 99%